The Legal Substance of Normative Ambiguity in Corporate Criminal Liability for Corruption - Mochamad Ananda Wyman Wahid; Hartiwiningsih Hartiwiningsih (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The corporate criminal culpability concept is point by point in Article 20, passage (1) of Law Number 31 of 1999 on the Annihilation of Debasement, as revised by Law Number 20 in 2001. Concurring to this article, on the off chance that a enterprise locks in in debasement, both the organization and/or its administration can confront criminal charges. The term